The contrary forces of innovation an ethnography of innovation in the food industry - Hoholm, Thomas (Palgrave Macmillan, 2011)
The complexity and tensions of industrial innovation processes are fleshed out through the analysis of an intriguing case study from the food industry. Drawing together insights from multiple disciplines, this book shows the controversial nature of innovation processes